Pembrolizumab in combination with bevacizumab and oral cyclophosphamide in heavily pre-treated platinum-resistant ovarian cancer. Issue 4 (5th January 2023) - Andrikopoulou, Angeliki; Liontos, Michalis; Skafida, Efthymia; Koutsoukos, Konstantinos; Apostolidou, Kleoniki; Kaparelou, Maria; Rouvalis, Angeliki; Bletsa, Garyfallia; Dimopoulos, Meletios-Athanasios; Zagouri, Flora
Abstract : Objective: Immune checkpoint inhibitors have been widely implemented in the treatment of solid tumors. Combinations of immune checkpoint inhibitors with chemotherapy, anti-vascular endothelial growth factor (VEGF) compounds, and poly-adenosine diphosphate-ribose polymerase inhibitors (PARP) are under evaluation in ovarian cancer. We aim to explore the efficacy of pembrolizumab in combination with bevacizumab and oral cyclophosphamide in patients with recurrent epithelial ovarian cancer. Methods: This was a retrospective study of all patients who received pembrolizumab in combination with bevacizumab and oral cyclophosphamide for recurrent platinum-resistant heavily pre-treated ovarian cancer in the Oncology Unit of Alexandra University Hospital from January 2021 to July 2022. Results: Median age at diagnosis was 56 years (SD 9.2; range 37–72). All patients were diagnosed with high-grade serous ovarian carcinoma. Initial disease stage was International Federation of Gynecology and Obstetrics (FIGO) IIIC in most cases (11/15, 73%). Patients were heavily pre-treated with a median of six (range 4–9) prior lines of systemic therapy. All patients experienced disease progression on first-line platinum-based chemotherapy, and median progression-free survival on first-line treatment was 22 months (95% CI 10.6 to 33.4). Patients received a median of four cycles of pembrolizumab in combination with cyclophosphamide and bevacizumab (range 3–20). Overall response rate was 13% (2/15) and disease control rate was 33% (5/15) with two patients achieving partial response and three patients achieving stable disease. Median progression-free survival was 3.5 months (95% CI 1.3 to 5.7) and the 6-month progression-free survival rate was 20%. Treatment was well tolerated with no dose-limiting toxicities. Conclusion: We showed that the combination of pembrolizumab with bevacizumab and oral cyclophosphamide is an effective alternative in heavily pre-treated patients with ovarian cancer who have otherwise limited treatment options.